Elementary-School Students' Use of Digital Devices at Home to Support Learning Pre- and Post-COVID-19 - Susan Sonnenschein; Michele Lee Stites; Hatice Gursoy; Jeniffer Khorsandian (MDPI AG, 2023)
As access to digital devices has grown, children in the United States are increasingly making use of digital devices at home. This paper reports two studies with data from two samples, one collected in 2017 and one in 2022, documenting how families of elementary-aged children make use of digital devices at home to support their children's learning in reading, writing, mathematics, and science. Of particular interest was whether parents have reported an increased use of digital devices since COVID-19. Data were collected both times via an online questionnaire, in which parents described their child's access to devices, amount of use, subject-specific use, and their own confidence and beliefs about device use. Most children made use of digital devices to support learning, but the extent of use varied by subject. Children's reported use of digital devices and parents' confidence assisting their children's learning with such devices reportedly increased from pre- to post-COVID. These findings can inform the efforts of researchers exploring the use of digital devices as a tool in the home learning environment and educators working with families already making use of these devices at home.